The E-Waste Problem of Nigeria & Proposed Solutions - Ufomba, I.C.; Jansz, Janis (World Safety Organization, 2013)
E-Waste disposal in Nigeria is poorly managed. The products of E-waste can cause adverse ill health effects if allowed to contaminate the soil, plants and water. This article identifies the current disposal practices and recommends more effective and safer ways to dispose of E-waste in Nigeria. The recommended disposal options are applicable to developing best practice for E-waste recycling, minimization, and safe disposal for countries worldwide.